Geo-blocking regulation: An assessment of its impact on the EU Digital Single Market - Georgios Alaveras; Néstor Duch-Brown; Bertin Martens (European Commission, Joint Research Centre (JRC), 2020)
In February 2018 the EU adopted the Geo-Blocking Regulation that prohibits any attempts to restrict consumer access to e-commerce websites on the basis of their nationality or country of residence. This paper seeks to evaluate the impact of that policy on crossborder e-commerce. We use page view data for about 10k e-commerce websites over the period February 2018 to October 2019, approximately 10 months before and after the entry into force of the regulation in December 2018. We classify the data in cross -border country pair traffic between countries of origin of visitors and countries of establishment of websites. Despite the fact that there may still be a significant amount of delivery restrictions in cross-border trade, we conjecture that any variation in traffic to e-commerce websites will correlate with variations in monetised e-commerce, even if modest. We find that the regulation increased real cross-border e-commerce activity inside the EU from 9.2% to 13%, depending on model specifications. It increased cross-border trade between EU consumers and e-commerce sites anywhere in the world by 11.2% to 11.9%. Applying different criteria for the definition of purely domestic websites slightly weakens the results for intra-EU cross-border trade and gives it a further boost for worldwide cro ss-border trade.
Keywords: 330; geo-blocking